Principles of hazardous materials management - Griffin, Roger D. (Environetbase., 2009)
Since the publication of the first edition of this volume in 1988, we have made great strides in reducing the amount of toxic waste that threatens our water, soil, and air. A greater acceptance of clean fuels and clean technologies, along with increased public awareness of environmental health hazards has given us greater optimism about the future of our planet. While few environmental threats can ever be completely eradicated, Principles of Hazardous Materials Management, Second Edition provides a framework for understanding the nature of hazardous materials and how the risks from such materials may be reduced. This long-awaited second edition updates and expands upon the topics in the bestselling first edition. The text begins with an introduction to hazardous materials, providing historical insight into toxins past and present. The book then explores the health effects of hazardous materials, discusses risk assessment, and profiles toxins in the air, soil, and water. The author examines the transportation and management of hazardous materials, defines waste characterization and analytical methods, and investigates waste treatment and disposal. Appendices contain the latest governmental regulations and a useful glossary. New to the Second Edition: Expanded information and new technologies for groundwater remediation New material on transportation and hazmat incidents More emphasis on proactive management as a technique for reducing hazardous waste generation Greater focus on the epidemiological model This volume provides the scientific background required to gain a working knowledge of toxic and hazardous substances. Comprehensive in scope yet concise enough to appeal to a wide range of professionals, it presents sufficient detail to ensure a firm understanding of the myriad concepts involved in hazardous materials management and how they.